An Analysis of Students’ Speaking Communication Strategies at The Eleventh Grade of The Computer and Network Engineering Programin SMK Teknologi YPL Lirik - Erina Gusranita; Widi Syaftinentias; Destri Wahyuningsih (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2026)
This study aimed to analyse the communication strategies used by the eleventh-grade students of the Computer and Network Engineering Program at SMK Teknologi YPL Lirik. The research employed a qualitative descriptive approach supported by quantitative data. Data were collected through a validated questionnaire consisting of 25 items based on Tarone’s (1980) taxonomy, which includes five strategies: avoidance, paraphrase, borrowing, mime, and appeal for assistance. Percentage formulas were used to quantify the frequency of each strategy, while qualitative interpretation was applied to explain patterns and pedagogical implications. The participants were 17 eleventh grade TKJ students selected through total sampling. The findings showed that the overall use of communication strategies reached 73.27%, categorized as Good. Among the strategies, appeal for assistance was the most frequently used (78.35%), followed by mime (75.88%) and paraphrase (74.62%). Meanwhile, avoidance (68.52%) and borrowing (68.00%) were categorized as fair good. These results indicate that students tended to rely on social and non-verbal compensatory strategies rather than independent linguistic strategies. The study concludes that communication strategies play an important role in supporting EFL speaking performance, and teachers are encouraged to integrate strategy training and communicative activities to help students develop greater speaking autonomy.